El paisaje rural y agrario en el desarrollo de la imagen del canton Urdaneta como destino agroturistico - Llumitaxi Alcivar, Andrea José (2020)
The present research work is the case study of the Urdaneta canton which belongs to the Province of Los Ríos, being one of the cantons with the greatest antiquity and cultural wealth. The case study that is being carried out in the mentioned city is focused on agrotourism, it will be promoted because there is a great need to create an analysis that allows to identify the agrarian spaces in the canton, and to be able to find self-sustainable tourism sources, this research is constituted by two variables the rural image and the analysis of the factors that influence the visits of tourists to the canton. Surveys were developed through field research, which focused on the rural area of the Urdaneta canton, which was developed using the finite population formula, using various research methods and techniques applied to data collection. The analysis performed is feasible due to the influence of people and the perception of each respondent, in addition to the direct observation made in each of the tourist centers of the rural area of the Canton.